ERP Adoption in Organizations The Factors in Technology Acceptance Among Employees - Shibly, Hamidur Rahaman; Abdullah, ABM.; Murad, Md Wahid (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book examines the factors that shape the adoption and continuous usage of new technology by employees in organizations. While within an organization new technology adoption has evolved from its traditional role to a more strategic one, the appropriate adoption of new technology can only add value to organizations. Identifying the factors that influence this adoption process is crucial for successful adoption of new technology in organizations. The study presented in this book focuses on individual, organizational, social, and industrial factors and uses those to offer a comprehensive model of Enterprise Resource Planning (ERP) application adoption. It contributes towards understanding employees' acceptance and adoption of enterprise-level technological innovation, allowing organizations to create a work environment conducive to individual implementation and acceptance of new technology. It appeals to researchers interested in studying the adoption of ERP and other innovative technologies in organizations. Hamidur Rahaman Shibly is a Senior Enterprise Data Architect at the Toronto Transit Commission, Canada. He has 20 years of professional IT experience in the areas of enterprise solutions, database architecture, application development and support. ABM Abdullah is a Lecturer of Project and Operations Management at the University of South Australia (UniSA). Prior to joining at UniSA, Abdullah worked as a teaching fellow at the University of North Texas' College of Business for more than two years. Md Wahid Murad, is a Lecturer at the University of South Australia. Prior to that he worked at the University of Adelaide in Australia and University of Malaysia Terengganu and Multimedia University in Malaysia. He published extensively in the high-quality journals, and his research works attracted a high number of citations to date.
1. ERP technology adoption - an introduction -- 2. Enterprise resource planning - an innovative technology -- 3. Adoption of innovative technology -- 4. ERP technology adoption - the factors -- 5. Research framework for technology adoption -- 6. Quantitative study on ERP adoption -- 7. Qualitative study on ERP adoption -- 8. ERP adoption model and discussion.
Keywords: Management; Information technology-Management.; Business information services; Technological innovations; Management; Business IT Infrastructure; Business Information Systems; Innovation and Technology Management